Pelaksanaan Cuti Mengunjungi Keluarga dan Cuti Menjelang Bebas Sebagai Hak Terhadap Narapidana di Lembaga Pemasyarakatan Kelas II A Pekanbaru - Apriani, Anita; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Implementation of the rights of prisoners in prisons is an obligation for the prison.Regulations concerning prisoners' rights contained in Article 14 of Law No. 12 of 1995concerning Corrections. Rights of prisoners is also a coaching process for prisoners inaccordance with the correctional system implemented after replacing of Imprisonment system.However, in reality many of the rights of prisoners who are not performing optimally, there iseven no rights given to prisoners. In this case relates to the implementation of the rights ofprisoners to inmates in prisons Class II A Pekanbaru. The purpose of this thesis, namely; first,the implementation of home leave (CMK) and leave towards free (CMB) against inmates inprisons Class II A Pekanbaru, second, CMK and obstacles in the implementation of the CMBagainst inmates in prisons II A Pekanbaru, third, the efforts made to overcome obstacles in CMKimplementation and CMB against inmates in prisons Class II A Pekanbaru.This type of research can be classified into types of socio-juridical research, because inthis study the authors conducted research on the spot directly under study in order to give acomplete and clear picture of the problem under study. This research was conducted in PrisonClass II A Pekanbaru, while the overall population and the sample is related to the issuesexamined in this study, the data sources used, the primary data, secondary data and data tertiarydata collection techniques in this study with the observation, questionnaire, interview andliterature study.From the research, there are three basic problems that can be inferred. first, theimplementation of the CMK and CMB against inmates in prisons Class II A Pekanbaru, thatright CMK in Prison Class II A Pekanbaru can not be given to prisoners and the CMB rights,these rights received less attention and do not run well. Secondly, the obstacles encountered inthe implementation of CMK and CMB against inmates in prisons Class II A Pekanbaru is thelack of knowledge of prison officers on the rights of prisoners, lack of personnel security prisonofficer, the requirements of the fulfillment of these rights are convoluted. Third, efforts are beingmade to overcome the obstacles in the implementation of CMK and CMB in Prison Class II APekanbaru, in the case of prisons give special permission to get out prison inmates to replaceCMK and facilitate the fulfillment of the requirements to get the right CMB. Suggestions author,first, the expected implementation of CMK and the CMB should be implemented and given themaximum, second barrier is the reason for not maximal CMK and CMB implementation shouldnot be a reason for non-fulfillment of these rights. Third, efforts were made Prison Class II APekanbaru in order to be implemented by not only planning only.Keywords: Implementation - Right - Prisoners - Prison